NIAT KONSUMEN LANSIA MENGONSUMSI SUPLEMEN MULTIVITAMIN YANG DIMODERASI MOTIF UNTUK SEHAT - Satrya Anggara Putra, Anak Agung Gede; Sri Suprapti, Ni Wayan; Kerti Yasa, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.02.TAHUN 2018DO - 10.24843/EEB.2018.v07.i02.p01, 2018)
The purpose of this study is to explain the influence of consumer attitudes, normative aspects, aspects of information, and perception of behavioral control on intentions of taking multivitamin supplements, as well as the role of motive for healthy as a moderating variable. The population in this study were the elderly who had the intention of taking multivitamin supplements. The technique of determining the sample was done by using purposive sampling method with 133 elderly people and domiciled in Denpasar as respondent . Questionnaire as research instrument and the moderated regression analysis as analysis technique in this research . The results showed that consumer attitudes and normative aspects had a negative and significant effect on intention of multivitamin supplement, while the information aspect and perception of behavior control had positive and significant effect on intention of multivitamin supplement. Motives for healthy are able to moderate the influence of consumer attitudes, normative aspects, aspects of information, and perceptions of behavioral control against intention to consume multivitamin supplements.